ANALYZING 21ST CENTURY SKILLS IN TEXTBOOK OF ENGLISH-SPEAKING TASK: A CASE AT VOCATIONAL HIGH SCHOOL - Waloyo, Edy (STIT Buntet Pesantren Cirebon, 2022)
In this Era, English textbook is still used as one of important sources in the teaching and learning process by the teachers. The contents of English textbook should fulfill students’ need and cover 21st skills which are useful for students in their future life. Hence, the analysis of English textbook is essential to be conducted. This research aims to describe the general overviews of two English textbooks and to describe 21st century skills are represented in the speaking task of vocational high school textbooks. This research used qualitative research and document analysis is used as technique of collecting data. Two English textbooks published by the Ministry of Education and Culture and Erlangga have good and very good content category, which is adapted by the Cunningsworth checklist. This means that two books have the capacity to be textbooks and in vocational high school for tenth grade. Moreover, both books have almost excellent category in learning and innovation skills or 4c skills like have lot of percent of Critical thinking, Communication, Collaboration and Creativity. And also have a lot percent in Life skills like FLIPS except Leadership.